Portada Análisis de las estrategias de comunicación utilizadas para la educación ambiental desarrolladas en el Parque Nacional Podocarpus, durante el periodo enero 2022 – julio 2023 - Padilla Jaramillo, Daniela Carolina (2024)
Ecuador is a multidiverse country in flora and fauna, with several protected areas, one of which is the Podocarpus National Park, located between the provinces of Loja and Zamora Chinchipe. In this sense, it is important to analyze the communication strategies implemented from the official Facebook page, a platform where publications of social interest are made alluding to environmental awareness, since communication strategies are essential to carry out an objective, an adequate design is necessary to achieve their execution. Based on the above, an analysis of the communication strategies used to promote environmental education and conservation developed in the Podocarpus National Park was carried out; likewise, their efficiency was determined and finally an alternative communication proposal directed to the citizens of La Paz was designed. The methodological process followed, in which a mixed approach was used, an observation sheet was applied to identify the communication strategies developed; also, through surveys it was possible to measure the effectiveness of the communication strategies, achieving the qualification of the knowledge of the citizens of Loja regarding the Park. The results obtained revealed shortcomings in the strategies addressed, thus revealing an issue such as the annual budget allocated. Likewise, a series of conclusions and proposals for improvement focused on the strategies used are presented. Keywords: Environmental communication; digital strategies; educommunication; environmental awareness; Podocarpus National Park.